2008
DOI: 10.4067/s0716-97602008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Methacholine and PDGF activate store-operated calcium entry in neuronal precursor cells via distinct calcium entry channels

Abstract: Neurons are a diverse cell type exhibiting hugely different morphologies and neurotransmitter specifications. Their distinctive phenotypes are established during differentiation from pluripotent precursor cells. The signalling pathways that specify the lineage down which neuronal precursor cells differentiate remain to be fully elucidated. Among the many signals that impinge on the differentiation of neuronal cells, cytosolic calcium (Ca2+) has an important role. However, little is known about the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…The store-operated Ca 2+ influx was higher in JOE cells, indicating that the mechanism responsible for the effect of golli on OPC proliferation was mediated through an increase in Ca 2+ influx through SOCCs. Recently, Cuddon et al (2008) reported that PDGF activates store-operated Ca 2+ entry in neuronal precursor cells, a finding that supports our data indicating that store-operated Ca 2+ uptake is an essential component of the PDGF mitotic mechanism in OPCs.…”
Section: Discussionsupporting
confidence: 92%
“…The store-operated Ca 2+ influx was higher in JOE cells, indicating that the mechanism responsible for the effect of golli on OPC proliferation was mediated through an increase in Ca 2+ influx through SOCCs. Recently, Cuddon et al (2008) reported that PDGF activates store-operated Ca 2+ entry in neuronal precursor cells, a finding that supports our data indicating that store-operated Ca 2+ uptake is an essential component of the PDGF mitotic mechanism in OPCs.…”
Section: Discussionsupporting
confidence: 92%
“…In this paper, we identified the channel responsible for this Ca ++ uptake increase in golli-overexpressing cells and we revealed for the first time that extracellular Ca ++ uptake through TRPC1 is an important component in the mechanism of OPC proliferation. Recently, Cuddon et al (2008) reported that PDGF activates store-operated Ca ++ entry in neuronal precursor cells, a finding that supports our data indicating that SOCCs are essential for neural cell division. Furthermore, several studies have shown that TRPC1 plays a role in Ca ++ influx and smooth muscle cell proliferation (Golovina et al, 2001; Sweeney et al, 2002a, b) and mediates Ca ++ influx activated by basic fibroblast growth factor (bFGF; FGF-2) in endothelial cells (Antoniotti et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…PDGF is known to exerts its action by triggering [Ca 2+ ]i transients in neuronal precursor cells(Cuddon et al, 2008), however, the mechanism of action remains less clear. Herein we report that PDGF-BB induced [Ca 2+ ]i elevations through activation of TRPC1.…”
Section: Discussionmentioning
confidence: 99%